Psychological Implications of Recreational Drug use among Students with Intellectual Disabilities in Nigeria - Bekomson, Achi Ndifon; Ofie, Sunday Maria; Emanghe, Emanghe Emmanuel; Agbongiasede, Catherine Kaning; Okeke, Stella Uchechukwu; Ameh, Eyiene; Obogo, Obogo Godwin; Moses, Egaga Musa; Ekaette, Samuel Okpon; Chukwurah, Margaret Uchenna; Omini, Ettah Ettah; Eteng, Matilda Ernest; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: The psychological consequences of drug use in individuals with intellectual disabilities can include worsened cognitive deficits, anxiety, aggression, depression, and impaired academic functioning. These effects are often underrecognized due to stigma or limited school support systems. Examine the psychological implications and patterns of recreational drug use among students with intellectual disabilities in Cross River and Akwa Ibom States, Nigeria. Five study objectives were stated to guide the research. Five research questions were formulated, and three hypotheses were stated. Literature was reviewed based on the variables under study. Method: The study adopted a descriptive survey research design. The study was conducted in Cross River and Akwa Ibom States, located in Nigeria's South-South geopolitical zone. The population comprises 1067 students with intellectual disabilities enrolled in public and private special education schools and inclusive education programs. Purposive and stratified random sampling techniques were used. A total sample of 200 respondents were selected for the study. Data was collected using a structured questionnaire. Experts validated the instruments, which were tested for reliability using the Cronbach Alpha reliability method. The test result revealed a reliability index of 0.80. Results of the research questions were presented using frequency counts, percentages, mean and standard deviation. Multiple linear regression was used to analyze the hypothesis. Results: The results revealed that substances such as marijuana, codeine, and tramadol were the most commonly reported. There is a significant relationship between recreational drug use and the psychological well-being of students with intellectual disabilities. Students with intellectual disabilities in Cross River State experience significantly higher psychological implications related to drug use compared to their peers in Akwa Ibom State. Peer influence and neighborhood environment are significant predictors of recreational drug use among students with intellectual disabilities, while family background is not. Conclusion: The findings of this study highlight a disturbing reality: students with intellectual disabilities are at substantial risk of psychological harm due to recreational drug use. Recommendation: Schools and disability support centers should implement peer-mentoring programs, social skills training, and anti-drug clubs that empower students to resist negative peer pressure.